Aktivitas Aktivitas Antibakteri Ekstrak Etanol 96% Pada Daun Tua Medang Pirawas (Litsea elliptica Blume) Terhadap Bakteri Staphylococcus aureus: Aktivitas Antibakteri Ekstrak Etanol 96% Pada Daun Tua Medang Pirawas (Litsea elliptica Blume) Terhadap Bakteri Staphylococcus aureus - SOLEHA, MARATU; AULIA RACHMA, FARADIVA; AGUSTINA, IKA; EFRILIA, MEGA; SYAHPUTRA, GURITNO (Jurnal Komunitas Farmasi Nasional, 2024)
Litsea elliptica Blume, is one type of traditional medicinal plant that is widely used by the Indonesian people. This symplisia can be used to treat headaches, fever, stomach ulcers, and also as an insect repellent. Litsea elliptica Blume also has antimicrobial and antioxidant properties. Objective: This study aims to determine whether 96% ethanol extract of Litsea elliptica Blume leaves has antibacterial activity against Staphylococcus aureus bacteria. Methods: This research is a laboratory experiment with descriptive quantitative method conducted in this study to test the antibacterial properties of 96% ethanol extract of Medang Pirawas (Litsea elliptica Blume) against Staphylococcus aureus bacteria. Results: The yield of the thick extract of Litsea elliptica Blume was 19.36 %, and the classes of secondary metabolite compounds found were phenols, flavonoids, saponins, tannins, alkaloids, and terpenoids. The results of the antibacterial activity test of the viscous extract of Litsea elliptica Blume did not show antimicrobial properties against the growth of Staphylococcus aureus, which was characterized by not forming a clear zone on the media. Conclusion: From these results it can be concluded that there is no antibacterial activity of ethanol extract of medang pirawas (Litsea elliptica Blume) leaves against the growth of Staphylococcus aureus bacteria.